3D Carbon Nanotubes Spaced Graphene Aerogel Incorporated with Prussian Blue Nanoparticles for Real-Time Detection of H2O2 Released from Living Cells. Issue 4 (17th February 2020) - Zhao, Peng; Zhao, Yanan; Jiang, Liuyi; Chen, Sha; Ji, Zhong; Hou, Changjun; Huo, Danqun; Yang, Mei
Abstract : Real-time detection of hydrogen peroxide (H2 O2 ) released from living cells is of great value in further understanding the occurrence process of some diseases and searching for new therapeutic strategies. However, selective monitoring of H2 O2 in living cells is still a huge challenge due to its low concentration, large diffusivity and high reactivity. Herein, three-dimensional carbon nanotubes spaced graphene aerogel incorporated with Prussian blue nanoparticles (3D PB NPs/G-CNTs) has been successfully synthesized via one-step mild temperature treatment, in which the PB NPs possess intrinsic peroxidase-like activity while the 3D porous structure of G-CNTs with large surface area and high conductivity can efficiently enhance catalytic performance. The composite exhibited good catalytic performances toward H2 O2 with a sensitivity of 134.3 μ A mM −1 cm −2 and a low detection limit of 95 nM in a linear range of 1–3161 μ M. Furthermore, the proposed sensor was successfully used for real-time detection of H2 O2 released from living cells, indicating the potential application of as-prepared 3D PB NPs/G-CNTs in monitoring the critical pathological process in living cells.